Characterization of casein kinase II of Trypanosoma (nannomonas) congolense. - Janoo, R.T.K. (University of Nairobi, 1993)
Casein kinase II from Trypanosoma congolense has been partially purified by chromatography on DEAE-cellulose and heparin-agarose and this subunit exhibits protein kinase activity with casein as the substrate. The enzyme adhered to both the DEAE-cellulose and heparin-agarose resins and was eluted at low salt concentration. Sequences of predicted amino acid domains of casein kinase II, which were conserved amongst sequences from a variety of species, were employed to construct degenerate oligomers. The oligomers were used in the polymerase chain reaction from which a 399 bp PCR product was obtained and sequenced. Using the PCR product to probe northern blots revealed a single transcript of 1.55 kb. This PCR product was also employed to screen an EMBL 3A subgenomic DNA library from the bloodstream form of Trypanosoma (Nannomonas) congolense. A clone containing a 1.2 kb sequence coding for a predicted protein of 400. amino acid residues was isolated. A partial sequence of this clone, encoding g,reater than 50% of the N-terminal part of the catalytic subunit was obtained. The deduced T congolense CK II catalytic subunit sequence reveals a high Degree of identity with the casein kinase II a and at sequence from both eukaryotes and plants: This sequence of T congolense.Cs; II a subunit displays a 69.1 % homology with the Zea mays CK II a subunit and a 66.8 % identity with the Caenorhabditis elegans a subunit chain. In addition, the T congolense catalytic subunit sequence revealed a 30 % homology with jhe human serine/threonine protein kinases. Comparison of the T congolense sequence with higher eukaryotic a and at sequences reveal that it is most identical with the a subunit.